The Effect of Local Food Consumption of Domestic Tourists on Sustainable Tourism in Bandung City - Eva Febriyanti; heppy Millanyani; Vigory Manalu (Lembaga Teewan Journal Solutions, 2026)
This study examines the relationship between domestic tourists’ local food consumption and Sustainable Tourism in Bandung City, Indonesia, using a framework adapted from Apak and Gürbüz (2023). Local food consumption is assessed through tourists’ Local Food Experience, which covers seven aspects: Exciting Experience, Cultural Experience, Health, Prestige, Taste/Quality, Price, and Interaction. Data were collected from domestic tourists who had visited Bandung City and consumed local food within the previous twelve months, then analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that Local Food Experience is positively associated with Economic, Socio-cultural, and Environmental Sustainability, with the strongest relationship found in the economic dimension. These results suggest that culinary tourism development should place greater emphasis on strengthening local food businesses, expanding employment opportunities for local communities, and promoting authentic culinary products. Clearer communication about local sourcing and waste-reduction practices is also needed to make the environmental value of local food consumption more visible to tourists.